Design, construction and monitoring of ecofriendly revetments for coastal protection / Shervin Motamedi - Shervin, Motamedi (2016)
Cutting of mangroves along the Malaysian coastlines has exposed these areas to tidal inundation and wave action. These areas have experienced severe erosion. Dikes have been constructed across the eroding coastlines to preserve these low-lying lands from flooding. Although these structures are often successful as rectification measures, they have negative impacts on the environment. It is essential to develop novel coastal protection methods that better integrate with the natural environment. The primary objective of this study was to propose innovative eco-friendly revetments for coastal protection. Based on the empirical methods, this study introduces the Double-layer and LEco revetments. Laboratory experiments and numerical models were used to verify the performance of the developed structures. A pilot project was carried out in a representative eroding site at the muddy coast of the Carey Island, Malaysia. This study introduced an integrated coastal rehabilitation program. A series of mangrove plantation works were established to rehabilitate the area towards a long-term trajectory restoration. Further, two indigenous species of coastal flora were planted on the revetments to include more green elements in the systems. A series of experiments evaluated the efficiency of the developed revetments. The innovative and sustainable LEco armoring unit (KD = 20) had a negligible displacement (< 7.8±0.1 mm), when used on the LEco revetment of q = 53°. Numerical study under various loading conditions was carried out for the developed revetments. Performance of the systems was evaluated to be safe based on the factors of safety against the high exit gradient (> 3), uplift pressure (> 1.5), and sliding (> 1.3). The study site was monitored for changes in topography and physical changes. Construction of the revetments was successful for establishing a state of equilibrium for the sediment deposition. This finding is important because the increase in sediment burial depth has a negative impact on mangrove rehabilitation works. Characterization of the near-surface soil stratum indicated that the site has a high buffer of silt and clay content (60-70%). This study carried out a series of mangrove rehabilitation works at two zones within the study site. Zone A was protected behind a detached breakwater and zone B was beyond the shelter of the structure. Measurements showed that six months after the beginning of the replanting works, the average mortality rate of the replanted mangroves for zone A (5.1±0.1 %) and B (45.8±0.1 %) decreased to 0.8±0.1 % and 12.3±0.1 %, respectively. Plantation of the coastal flora species exhibited a negligible mortality rate, when planted on the deck of the revetments. These findings suggest that the rehabilitation works were successful. In conclusion, the proposed integrated coastal rehabilitation program was efficient in providing a calm area to shelter the replanted mangroves. The revetments facilitated the growth of coastal vegetation by establishing an equilibrium state. The site is representative of the majority of areas along the coastlines of the West Malaysian Peninsular. Therefore, the findings can be a gear towards mitigating coastal erosion and mangrove degradation problems at similar sites.